Adaptive array processing MLSE receivers for TDMA digital cellular - Molnar, K.J (IEEE Journal on selected areas in communications)
Array processing is a promising approach for improving quality, coverage, and capacity in digital cellular communication systems. By combining array processing with maximum likelihood sequence estimation (MLSE), intersymbol interference (ISI) introduced by multipath propagation can be mitigated as well. Novel symbol-spaced and fractionally spaced adaptive array processing MLSE receivers are developed for both diversity and phased array antenna configurations. The practical issues of synchronization and channel estimation are addressed. A novel approach to automatic frequency error correction (AFC) is proposed and is shown to be critical when cancelling cochannel interference. Performance is evaluated for the reverse link of the IS-136 TDMA-based digital cellular system. Substantial improvements are obtained over conventional antenna configurations for receiver sensitivity (2.5-4 dB) and over traditional antenna combining when cochannel interference is present (0.5-25 dB)